2023
DOI: 10.3389/fpubh.2022.1035398
|View full text |Cite
|
Sign up to set email alerts
|

Research on elderly users' intentions to accept wearable devices based on the improved UTAUT model

Abstract: IntroductionAs the proportion of the world's elderly population continues to increase, wearable devices can provide ideas for solving a series of problems caused by population aging. Therefore, it is of great significance for the development of intelligent elderly care and the improvement of the quality of elderly care services to explore the factors that influence the intention of elderly users to accept wearable devices.MethodsAn improved unified theory of acceptance and use of technology (UTAUT) model is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 74 publications
2
9
0
Order By: Relevance
“…Performance expectations have a positive effect on behavioral intentions, which result is consistent with previous findings [ 32 , 33 , 34 , 35 , 36 ]. The performance expectation factor has the largest effect other than behavioral intention, and Sun et al [ 74 ] showed that the higher the performance expectation, the stronger the willingness to use, which verifies the UTAUT model.…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…Performance expectations have a positive effect on behavioral intentions, which result is consistent with previous findings [ 32 , 33 , 34 , 35 , 36 ]. The performance expectation factor has the largest effect other than behavioral intention, and Sun et al [ 74 ] showed that the higher the performance expectation, the stronger the willingness to use, which verifies the UTAUT model.…”
Section: Methodssupporting
confidence: 92%
“…Perceived cost has a negative impact on behavioral intention, which result is consistent with previous findings [ 31 , 34 , 55 , 56 ]. It has been indicated that factors such as excessive monetary, learning and time costs significantly reduce the behavioral intention of the aged to use smart aged-care products.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…Studies have examined the influence of aesthetic appeal on behavior within the context of website design. Research has explored the impact of customers' perceptions of the visual landscape of online shopping electronic services on the perceived value of electronic shopping and customer loyalty, emphasizing the potential influence of aesthetic appeal on consumer behavior [166,167]. Aesthetic appeal has been found to have a small but significant impact on participants' intention to revisit or recommend a website, indicating its potential influence on behavioral control [168].…”
Section: Research Methods and Hypothesismentioning
confidence: 99%
“…However, little is known about the psychological mechanisms underlying the effects of smartwatch attributes on continued exercise intentions. Specifically, previous studies mainly focused on the effect of smartwatch attributes on smartwatch adoption by relying on the technology acceptance model (TAM) or its variations (e.g., extended technology acceptance model [ETAM]) [7][8][9][10][11][12][13][14]. Although these studies provide meaningful insight into how an individual initially adopts wearable-device technologies, it is also imperative to understand what smartwatch attributes help individuals engage in exercise and physical activities when considering such devices' main usage (i.e., healthcare) [15,16].…”
Section: Introductionmentioning
confidence: 99%